A Study of the Relationship between Safety Perceptions and Mindfulness - UĞURAL, MEHMET NURETTİN (ADAMOR Toplum Araştırmaları Merkezi, 2023)
It is well known that the construction industry has a high rate of workplace accidents, resulting in complex legal situations and legal cases. Researchers are debating whether the majority of workplace accidents and injuries are the result of employees' unsafe work practices or unsafe working conditions. In this context, it has been determined that we must comprehend the trait predictors of safety behaviors, which influence workplace accidents and injuries. This study's primary objective is to identify the factors that influence safety behavior in construction workplaces. In previous studies, the effects of employee perceptions of safety culture on safety behavior performance were typically measured with the aid of various mediators. This study, unlike previous ones, focuses on revealing the mediating effect of employee mindfulness perceptions in the relationship between safety culture and safety behavior. Using a sample of 387 employees from the Turkish construction industry, a 58-item survey was conducted to determine the impact of safety culture perception and mindfulness on self-reported safety behavior. A structural equation model was used to analyze and explain the relationships between the proposed framework's constructs. The results of the study indicate that safety culture is associated with safety behavior, and that mindfulness mediates this relationship. There are significant relationships between employees' perceptions of safety culture, mindfulness, and safety behavior, according to the findings. Safety culture and mindfulness are significant predictors of safety behaviors, and mindfulness is an essential personal resource for a successful safety-focused organization.
Keywords: Organizational Culture; Mindfulness; Safety Behaviors; Project Management; Civil Engineering